Efisiensi Penggunaan Faktor-Faktor Produksi Pada Usaha Tani Kelapa Sawit Rakyat (Elaeis Guineensis Jacq) (Studi Kasus: Desa Tanjung Medan, Kec. Kampung Rakyat Kab. Labuhanbatu Selatan) - Apriliyani, Kiki; Nasution, Myrna Pratiwi (Universitas Medan Area, 2022)
One of the steps that can be taken to increase the income of oil palm farmers is to use production inputs as efficiently as possible, in order to maximize the profits obtained by oil palm farmers. An increase in oil palm production can be achieved if the use of production inputs is used efficiently. Efficient oil palm farming will encourage the optimal use of production factors, of course, will determine the achievement of technical efficiency, allocative efficiency/price and economic efficiency in oil palm farming. The purpose of this study was to analyze technical efficiency, allocative efficiency/price and economic efficiency in smallholder oil palm farming in Tanjung Medan Village, Kec. District People's Village. South Labuhanbatu. The data obtained during the research were processed using the stochastic frontier 4.1 production function method and Ms. Excel. The research data were taken from 60 farmer respondents. The results showed that the average level of technical efficiency obtained was 76.66 percent of the maximum productivity. The average value of allocative efficiency/price as a whole is 0.33. The average value of economic efficiency obtained is 0.30 in smallholder oil palm farming in Tanjung Medan Village, Kec. District People's Village. South Labuhanbatu.